Kontribusi Presentase Ketebalan Lemak Tubuh dan IMT Terhadap Physical Fitness Index Atlet Judo PPLP Jawa Tengah (Indonesian Journal for Physical Education and Sport, 2021)
Several sports, especially judo, with a high body posture and good physical condition will support the achievement of high sports achievements, such as fat thickness and BMI. This study aims to determine the percentage of body fat thickness and BMI PhysicalFitness Index in Central Java PPLP Judo athletes and the contribution of percentage body fat thickness and BMI to PhysicalFitness Index in PPLP Central Java Judo Athletes 2020. The data collection method uses survey tests. The subject of the study was athletejudo PPLP Central Java 2020. The results of the study on the percentage of body fat thickness against the physical fitness index obtained a t-count value of -2.878 more than the t-table. The results of the BMI study on physical fitness index showed that the t-count value of -2.656 was more than the t-table. Based on the results, it was concluded that the contribution of body fat thickness to physical fitness index was significant and it can be concluded that the contribution of BMI to physical fitness index was significant.